Pengaruh Jenis Filter Udara Terhadap Torsi, Daya, dan Konsumsi Bahan Bakar: The Effect of Air Filter Type on Torque, Power, and Fuel Consumption - Putu Agus Hendrawan; Nyoman Arya Wigraha; Gede Wiratmaja; Edi Elisa (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the effect of variations in air filter materials on torque, power, and fuel consumption in a Honda Beat 110 cc fuel-injected motorcycle. The air filter materials used in this study include paper, sponge, cotton, and wire mesh, each having different porosity characteristics that are expected to influence the amount of air entering the combustion chamber and consequently affect engine performance. This research employed an experimental method with a quantitative approach. Torque and power tests were conducted using a dynamometer, while fuel consumption was measured based on the amount of fuel used at specific engine speeds. The data were collected through repeated tests and analyzed statistically to determine the effect of air filter material variations on the observed parameters. The results are expected to reveal differences in torque, power, and fuel consumption among the various air filter materials and to identify the most effective filter material for improving engine performance while maintaining fuel efficiency.